Submucosal gland mucus strand velocity is decreased in chronic rhinosinusitis. Issue 4 (10th January 2018) - Tipirneni, Kiranya E.; Zhang, Shaoyan; Cho, Do‐Yeon; Grayson, Jessica; Skinner, Daniel F.; Mackey, Calvin; Moore, Lindsay; Cole, Denzel; Banks, Catherine G.; Woodworth, Bradford A.
Abstract : Background: Chronic rhinosinusitis (CRS) may be initiated by innately impaired host defense mechanisms that predispose the upper airways to infection. Recent evidence suggests tethering of submucosal gland mucus strands represents an inciting event within cystic fibrosis (CF) airways, occurring prior to onset of chronic infection. Submucosal gland hypertrophy and defective mucociliary clearance (MCC) are present in actively inflamed sinuses, but mucus strand velocity may also be affected as a secondary event, further contributing to chronic disease. The objective of this study is to assess whether mucus strand velocity is decreased in patients with CRS. Methods: Mucosal explants from patients with and without CRS were submerged in Ringer's solution mixed with fluorescent nanospheres. Methacholine was then added, and videos demonstrating strand growth and detachment were generated from a time‐lapse of Z‐stack images using a multiphoton confocal microscope. Dynamic mucus strands were identified and individual velocities quantified with the MTrackJ plug‐in of ImageJ. Results: Fifteen patients met criteria for ex vivo analysis of mucus strand velocities (CRS, n = 9 vs controls, n = 6). Mucus strands were recorded (pixels/second) streaming from the submucosal gland openings. Average mucus strand velocities were significantly decreased in patients with CRS (1.53 ± 0.67 vs controls, 4.86 ± 1.68 pixels/second; p < 0.001). Conclusion: This study is the first to report evidence of abnormal mucus strand velocity from submucosal glands in diseased sinonasal mucosa. Future pharmacologic studies targeting this critical component of MCC are warranted.